Assessment of Smell Function in Syndromic Craniosynostosis Patients. Issue 6 (September 2016) - Vaughan, Casey; Attlmayr, Bernhard; Dalton, Lucy; Upile, Navdeep; Xie, Carol; De, Su
Abstract : Abstract: Craniosynostosis is defined as premature fusion of the cranial suture lines and is part of a syndrome in 15% to 40% of the patients. There is limited literature available regarding these children's ability to smell. Most of them will undergo numerous surgical procedures, some of which may alter their sense of smell, potentially leading to significant social as well as safety implications. Ethical approval was obtained for this pilot study. Children with syndromic craniosynostosis were recruited and underwent anterior rhinoscopy, prior to performing a smell test utilizing the Sensonic pediatric Smell wheel. The results were compared to an age-matched control group. Eight children with syndromic craniosynostosis participated in the study. Of a possible total score of 11, their mean average score was 6.6 and the median was 6. In comparison, the mean average score for the control group was 7.5 and the median was 7. Although the study group was small, this pilot study demonstrates that children with syndromic craniosynostosis have a similar ability to identify smells to an age-matched cohort. Further research can now be undertaken to see whether or not midface advancement procedures affect these children's sense of smell.